PERLINDUNGAN NEGARA TERHADAP HAK KEBEBASAN PRIBADI DALAM PERSPEKTIF HAK ASASI MANUSIA - ahmad nikhrawi hamdie (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2018)
The concept of human rights is a long-standing thing in human life on earth. The study of human rights in the form of thought has existed since the time of the Greeks. In Indonesia Law No. 39 of 1999 on Human Rights states that human rights are a set of rights that are inherent in the nature and existence of human beings as creatures of God Almighty and is a gift that is obliged to be respected, upheld and protected by the State, government and every person for the honor and protection of human dignity and dignity. The freedom of personal belonging to it which represents independence presupposes public opinion without interference, obstacles, interference and pressure. In practice there are still rulers who do not provide a good room for the delivery of this right. Enforcement of the rules of freedom of expression is still a struggle so that the goal can be achieved.